Technologies of Collection: Railroads and Cameras - Shaw, Wendy (Possessors and Possessed, 2003)
The process of antiquities collection in the Ottoman Empire unfolded in the context of the acquisition of technologies and practices that were new and exciting not only in the empire but in the entire world as well. The reformulation of archaeology as a large-scale science depended heavily on new modes of transportation, such as the railroad, both for people and for cargo. Similarly, photography provided new modes of documentation and transport of information. Together, these technologies transformed the ways in which cultures could be recorded and disseminated. The Ottoman Empire acquired these technologies, invented in Europe, at the cost of